Comparative Gene Expression Analysis of Lymphocytes Treated with Exosomes Derived from Ovarian Cancer and Ovarian Cysts - Li, Yujuan; Yang, Yang; Xiong, Aiwei; Wu, Xiaoqin; Xie, Jingyan; Han, Suping; Zhao, Shuli (Frontiers in Immunology, 2017)
Cancer cells employ many strategies to evade immune defense and to facilitate tumor growth and angiogenesis. As a novel mode of intercellular communication, cancer-derived exosomes contribute to the recruitment and reprogramming of lymphocytes within the tumor environment. However, the mechanisms and key molecules mediating the effect of exosomes on lymphocytes are unclear. We treated healthy peripheral blood lymphocytes (PBLs) with exosomes from ovarian cancer and ovarian cysts and screened for differentially expressed genes using the RT2 Profiler Cancer Inflammation & Immunity Crosstalk PCR Array. A total of 26 upregulated genes (mainly pro-inflammatory genes and immunostimulatory and immunosuppressive factors) and 2 downregulated genes (antigen presentation HLA-A/B) were identified. Western blotting using lymphocytes from malignant ascites and peritoneal washings of benign ovarian cysts suggested that the interferon and NFκB signaling pathway are involved in the immune regulation of malignant exosomes. Out of 28 differentially expressed genes detected using the array, 11 were validated by real-time PCR using lymphocytes within ovarian cancer (n = 27) and ovarian cyst (n = 9) environments. In conclusion, our results indicated that malignant cells secrete exosomes in the tumor microenvironment to recruit lymphocytes in order to suppress antitumor immunity (IL10, Foxp3, and HLA-A/B) and enhance tumor invasion, angiogenesis, and dissemination of proinflammatory cytokines (such as IL6 and VEGFA) via the interferon and NFκB signaling pathways. These results clarify lymphocyte-cancer cell crosstalk via exosomes and may facilitate the development of effective immunotherapeutic strategies for ovarian cancer.